(untitled) (Bangladesh Journal of Pharmacology, 2022)
The compounds 1,3,4-oxadiazole derivatives (1-8) were synthesized by the cyclization of 4-hydroxy benzhydrazide (1) with various substituted aroma-tic aldehydes (2) using FeCl3 as catalyst and methanol as a solvent medium. The structures of the newly synthesized compounds were assigned based on FT-IR, 1H-NMR, and mass spectral data. In vivo antidepressant activity was performed by tail suspension test and forced swimming test models. Using the Schrodinger Maestro, the in silico analysis was performed and docked to the glycogen synthase kinase 3β binding site (PDB: 3GB2). Compounds 8 [4,4’-(1,3,4-oxadiazole-2,5-diyl)diphenol] and 3 [3-(5-(4-hydroxyphenyl)-1,3,4-oxadiazol-2-yl) phenol] showed both potent inhibitory activity against GSK-3β with a docking score of -7.800 kcal/mol as well as good antidepressant activity in both tail suspension and forced swimming tests models. The synthesized derivatives showed good antidepressive potential.